2019
DOI: 10.1016/j.biopsych.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Error Processing and Inhibitory Control in Obsessive-Compulsive Disorder: A Meta-analysis Using Statistical Parametric Maps

Abstract: Error-processing and inhibitory control in obsessive-compulsive disorder: a meta-analysis using statistical parametric maps. Biological psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
107
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 99 publications
17
107
3
1
Order By: Relevance
“…consistent with other literature of alterations in circuits (e.g., frontostriatal, cingulo-opercular) supporting cognitive control processes in OCD (e.g., refs. [22][23][24][25]. Thus, we hypothesized that 1) relative to matched healthy participants, unmedicated patients with OCD would show increased conflict-related responses in frontostriatal and cingulo-opercular (e.g., insula, anterior cingulate cortex [ACC]) regions and 2) such activity would predict EX/RP outcomes.…”
Section: Significancementioning
confidence: 99%
“…consistent with other literature of alterations in circuits (e.g., frontostriatal, cingulo-opercular) supporting cognitive control processes in OCD (e.g., refs. [22][23][24][25]. Thus, we hypothesized that 1) relative to matched healthy participants, unmedicated patients with OCD would show increased conflict-related responses in frontostriatal and cingulo-opercular (e.g., insula, anterior cingulate cortex [ACC]) regions and 2) such activity would predict EX/RP outcomes.…”
Section: Significancementioning
confidence: 99%
“…The regions identified here are known to be differentially activated to errors across a variety of cognitive tasks and populations (Neta et al, ; Norman et al, ). This is in keeping with the notion that premature responses are brought about by failure of control processes.…”
Section: Discussionmentioning
confidence: 96%
“…26 Furthermore, a recent meta-analysis reported that activity in the ventral ACC is significantly reduced during inhibitory control. 27 The posterior cingulum is one important cluster of the default mode network. It is widely accepted that this network plays an important role in emotion processing and self-referential activity, including introspection.…”
Section: Discussionmentioning
confidence: 99%